Higher carbohydrate intake is associated with increased risk of all‐cause and disease‐specific mortality in head and neck cancer patients: results from a prospective cohort study. Issue 5 (17th April 2018) - Arthur, Anna E.; Goss, Amy M.; Demark‐Wahnefried, Wendy; Mondul, Alison M.; Fontaine, Kevin R.; Chen, Yi Tang; Carroll, William R.; Spencer, Sharon A.; Rogers, Laura Q.; Rozek, Laura S.; Wolf, Gregory T.; Gower, Barbara A.; et al.
Abstract : No studies have evaluated associations between carbohydrate intake and head and neck squamous cell carcinoma (HNSCC) prognosis. We prospectively examined associations between pre‐ and post‐treatment carbohydrate intake and recurrence, all‐cause mortality, and HNSCC‐specific mortality in a cohort of 414 newly diagnosed HNSCC patients. All participants completed pre‐ and post‐treatment Food Frequency Questionnaires (FFQs) and epidemiologic surveys. Recurrence and mortality events were collected annually. Multivariable Cox Proportional Hazards models tested associations between carbohydrate intake (categorized into low, medium and high intake) and time to recurrence and mortality, adjusting for relevant covariates. During the study period, there were 70 deaths and 72 recurrences. In pretreatment analyses, high intakes of total carbohydrate (HR: 2.29; 95% CI: 1.23–4.25), total sugar (HR: 3.03; 95% CI: 1.12–3.68), glycemic load (HR: 2.10; 95% CI: 1.15–3.83) and simple carbohydrates (HR 2.26; 95% CI 1.19–4.32) were associated with significantly increased risk of all‐cause mortality compared to low intake. High intakes of carbohydrate (HR 2.45; 95% CI: 1.23–4.25) and total sugar (HR 3.03; 95% CI 1.12–3.68) were associated with increased risk of HNSCC‐specific mortality. In post‐treatment analyses, medium fat intake was significantly associated with reduced risk of recurrence (HR 0.08; 95% CI 0.01–0.69) and all‐cause mortality (HR 0.27; 95% CI 0.07–0.96). Stratification by tumor site and cancer stage in pretreatment analyses suggested effect modification by these factors. Our data suggest high pretreatment carbohydrate intake may be associated with adverse prognosis in HNSCC patients. Clinical intervention trials to further examine this hypothesis are warranted. Abstract : What's new? Chowing down on carbohydrates could make things worse for those with head and neck cancer, new results show. In this prospective study, the authors collected pre‐ and post‐treatment diet information from HNSCC patients by questionnaire, and collected recurrence and mortality data each year. They found that high pretreatment intake of total carbohydrates and total sugar were associated with increased mortality from HNSCC. Post‐treatment, fat intake was associated with reduced mortality. This is the first epidemiologic study to look for an association between carbohydrate intake and HNSCC mortality.